Characterization of Prodiginine Pathway in Marine Sponge-Associated Pseudoalteromonas sp. PPB1 in Hilo, Hawai‘i - Sakai-Kawada, Francis E.; Ip, Courtney G.; Hagiwara, Kehau A.; Nguyen, Hoang-Yen X.; Yakym, Christopher-James A. V.; Helmkampf, Martin; Armstrong, Ellie E.; Awaya, Jonathan D. (Frontiers in Sustainable Food Systems, 2020)
Marine sponge tissue samples were collected from Puhi Bay off the Eastern shore of Hilo, Hawai‘i. The sponge was identified as Petrosia sp. and possessed red pigmentation. Associated microorganisms were isolated via surface sterilization and aseptic plating of sponge tissue samples. One isolate (PPB1) produced a colony with red pigmentation like that of Petrosia sp. 16S characterization and sequencing revealed that the isolate belonged to the Pseudoalteromonas genus. Biological assays of Pseudoalteromonas sp. PPB1 crude extract demonstrated both antimicrobial and antioxidant activity. The draft genome was sequenced, assembled, and annotated. The genome revealed a prodiginine biosynthetic pathway and the first cited-incidence of a prodiginine-producing Pseudoalteromonas species isolated from a marine sponge host. Further understanding of the bioactivity and biosynthesis of secondary metabolites like prodiginine may uncover the ecological interactions between host sponge and microorganism.